The Role of AI in Enhancing Healthcare Access and Service Quality in Resource-Limited Settings - Farhat, Rehman; Abideen Malik, Ahmad Raza; Sheikh, Abdullah Hussain; Noor Fatima, Ayesha (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
The integration of Artificial Intelligence (AI) in healthcare has become a critical factor in improving healthcare delivery, particularly in resource-limited environments. In countries like Pakistan, where healthcare access is a major challenge, AI-powered solutions such as telemedicine, diagnostic tools, and health chatbots have the potential to revolutionize healthcare service delivery. This research aims to explore the effectiveness of AI in improving healthcare access, diagnosis time, and service quality, while identifying the challenges faced in its implementation. A mixed-methods approach was employed, utilizing surveys, interviews, and case studies with healthcare professionals, AI developers, and patients in both rural and urban areas. The findings revealed that AI-driven solutions significantly enhanced healthcare access, particularly in rural areas, by enabling remote consultations and reducing diagnostic time. However, challenges such as infrastructure limitations, low technology literacy, resistance to adoption, and the absence of robust policy frameworks were identified as key barriers to successful AI integration. The study suggests that improvements in technological infrastructure, training, and regulatory frameworks are essential for maximizing the impact of AI in healthcare. Future research should focus on exploring the long-term effects of AI on patient outcomes, investigating the role of policy in AI adoption, and examining how AI can be adapted to different cultural contexts in healthcare systems globally.